Crises and opportunities the shaping of modern finance - Cassis, Youssef (Oxford : Oxford University Press, 2011)
Examining the differences and commonalities of eight global financial crises since the late 19th century (including the Great Depression of the 1930s and the financial debacle of the early 21st century) this book provides insights into how the financial landscape has - or has not - been reshaped after a systemic shock.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Financial crises -- History; Financial services industry -- History; Business cycles -- History